Cable/deadpool (2004), volume 2 ebook The burnt offering - special. - Nicieza, Fabian (Cable/Deadpool (2004),, 2011)
Collects Cable/Deadpool (2004) #7-12. A floating city promises hope for humans and mutants alike! But if Cable plans to be Earth's Savior, will Deadpool accept the role of betrayer?